Religious Discourses and Policies Towards the Palestinian-Israeli Conflict: A Comparison of Turkey and Iran - MERCAN, MUHAMMED HÜSEYİN (My University, 2021)
Considering that Palestinian-Israeli conflict is one of the cases in the current international system that is predominantly shaped by the religion factor, it is an important question how and to what extent both Turkey and Iran legitimize their strategies using religious discourse. Although both states rely on Islamic beliefs in their approaches towards the cause of Palestinians and both utilize religious rhetoric extensively to shore up their domestic support, they differ in how in their discourses and policies towards Israel. In this regard, the study first discusses the current literature on the role of religion in foreign policy and international relations. Then, how religious values and beliefs have informed the foreign policy discourse and behavior of Turkey and Iran with specific focus on the Palestinian-Israeli issue are discussed.

Mevcut uluslararası sistemde din-siyaset ilişkisinin en açık şekilde görüldüğü vaka olarak Filistinİsrail meselesi düşünüldüğünde hem Türkiye hem de İran’ın dini referanslar yoluyla hayata geçirdikleri stratejileri nasıl ve ne düzeyde meşrulaştırdıkları önemli bir sorudur. Özellikle tarafların Filistin yaklaşımları benzer olmakla beraber her iki ülkenin İsrail’e yönelik tavır ve söyleminde dini referansların kullanımının boyut değiştirmesi bu karşılaştırmayı daha anlamlı hale getirmektedir. Bu bağlamda makalede öncelikle dinin dış politika ve uluslararası ilişkilerdeki rolüne dair gelişen literatürün bir tartışması yapılacak sonrasında ise Türkiye ve İran’ın Filistin-İsrail meselesini dini argümanlar üzerinden nasıl gördüğü ardından da her iki ülkenin bu meseleye yaklaşımında dinin nasıl bir rolü olduğu derinlemesine tartışılacaktır.
Filistin- İsrail Çatışmasına Yönelik Dini Söylem ve Politikalar: Türkiye ve İran Üzerine Bir Karşılaştırma
Keywords: Turkey; Iran; Religion; Foreign Policy Discourse; PalestinianIsraeli Conflict; Türkiye; İran; Din; Dış Politika Söylemi; Filistin-İsrail Çatışması